COVID on Campus: Assessing the Impact of the Pandemic on Undocumented College Students - Laura E. Enriquez; William E. Rosales; Karina Chavarria; Martha Morales Hernandez; Mercedes Valadez (SAGE Publishing, 2021)
This article examines the initial impact of the COVID-19 pandemic on undocumented college students. Deploying an ecological framework, we situate students' experiences within their families, communities, and educational institutions. We draw on qualitative and quantitative survey responses from 1,067 undocumented students attending California 4-year universities. Qualitative findings show that immigration status exacerbated the negative economic effects of the pandemic, leading to severe financial strains that had cascading negative effects on undocumented students' academics and health. Regression analyses confirm the strong association between students' preexisting economic insecurity and negative effects of the pandemic. Legal vulnerability and family strains moderated this relationship, but campus environment had little effect.